THE REALIZE EQUITABLE TEACHER PROTECTION THROUGH A NON-PENAL POLICY - Serah, Yenny Aman; Setiawati, Rini (International Journal of Law Reconstruction, 2022)
Teacher protection has been regulated in various laws and regulations, both laws, government regulations to ministerial regulations, but the reality of teachers is still faced with problems, including the weak legal protection. Facts are revealed when problems are encountered, such as teachers experiencing criminalization with allegations of committing violence in the learning process, teachers must face the legal process themselves, and there is no mechanism for handling them. In order to realize equitable teacher protection, this study uncovers the problem of how to develop a model to realize equitable teacher protection through a non-penal policy approach. This research was used the transdisciplinary approach involving several stakeholders through the sociological juridical research method, the results of research on the importance of being regulated by regional policies were obtained through the establishment of the Legal Service and Teacher Protection Unit (UPHPG) which is a coordinating institution to solve the problem of criminalizing teachers by prioritizing non-penal policies. The non-penal policy in handling the problem of teacher criminalization through UPHPG is formulated an integral and comprehensive handling mechanism involving several stakeholders and prioritizing prevention efforts through communication, information and education to all parties, providing consultation and legal assistance as well as legal assistance services to good teachers.